Subdifferentials of perturbed distance function in Riemannian manifolds. (2nd November 2018) - Barani, A.
ABSTRACT: The notions of perturbed optimization problem and perturbed distance function are introduced in Riemannian manifolds. Some characterizations of Fréchet and proximal subdifferentials of perturbed distance function in the context of Riemannian manifolds are given.